Cyclic Voltammetric Analysis of Retinol in Facial Serum - Putra, Ananta Adita Eka; Setiarso, Pirim (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Retinol is an active compound within the retinoid group, derived from vitamin A and characterized by the presence of a cyclohexenyl ring structure. It is commonly incorporated into cosmetic formulations, particularly facial serums. To ensure product safety and efficacy, facial serums containing retinol must comply with established concentration limits to avoid overclaiming. Various analytical methods have been developed and utilized to determine retinol concentration. This research focuses on determining the amount of retinol present in facial serum by employing the cyclic voltammetry technique.. Cyclic voltammetry is an electrochemical method employed to evaluate the activity of specific compounds in solution by measuring the current generated between two electrodes as a function of the applied potential, which is cyclically varied from an initial to a final value and back again. In this study, the analysis was performed using a carbon paste electrode modified with ZnO and TiO₂ nanoparticles in a ratio of 3:2:3:2. The measurement of retinol in facial serum was carried out using a 5000 ppm KCl solution as the supporting electrolyte, phosphate buffer solution at pH 5, a deposition time of 20 seconds, and a scan rate of 0.25 V/s. The retinol concentration in the serum samples was determined based on a standard calibration curve described by the linear equation y = 0.0000355x + 0.00137, with a correlation coefficient of R = 0.99979, indicating excellent linearity. Based on the calibration curve, the retinol concentrations in the facial serum samples were found to be 0.023% for brand A, 0.021% for brand B, and 0.022% for brand C with a LoD value of 0.001 ppm and a LoQ value of 0.003 ppm. The findings indicate that cyclic voltammetry has the potential to be widely applied in routine quality control within the cosmetic industry, offering an efficient and cost-effective analytical solution to ensure the stability and effectiveness of active ingredients in cosmetic products.